Lean thinking to improving access to cancer patients in a Public General Hospital - Pinto, Carlos Frederico; Coelho, Stela Maris; Marotta, Evelin Araujo; Reis, Sheila Vianna; Calado, Robisom Damasceno; Silva, Messias Borges (Journal of Innovation and Healthcare Management, 2015)
Unbalanced treatment scheduling and overcrowding is a common problem for cancer centers in Brazil, with huge access restrictions due to system inefficiencies and poor assistance design. The purpose of this report is to show how lean thinking can be applied to healthcare by using lean methods and production leveling. The case study / report presented was adopted in order to describe the approach, techniques and findings of this project, as part of a lean initiative. Lean Value Stream Mapping tools and leveling tools improved unit performance by increasing unit capacity freeing treatment slots by leveling and decrease of waiting time for cancer treatment .The process redesign also eliminated unnecessary movement and overtime.